DIGITAL MARKETING TRAINING: Strategies to Increase Sales in Indonesian Market Place - Monica Elizabet (Jurnal PKM Manajemen Bisnis, 2022)
The presence of the digital market provides fresh air for small and medium businesses. The reason is, if they are able to take advantage of this, they can reach many consumers throughout Indonesia. However, it takes knowledge and skills in digital marketing, namely the ability to open an online store, create advertisements, promotions, and use social media. Based on this phenomenon, this service activity is carried out to be able to provide briefing to small and medium business actors on how to make sales online with relevant strategies. The activity method consists of two things, the first is theoretical (lectures) and the second is in the form of training. This activity is carried out on micro-enterprises in the South Tangerang city area under the guidance of the Cooperatives Service. The results of the activity are technical explanations and also practices about creating online stores, searching for products from international market places, placing paid advertisements on social media and digital markets, creating organic promotional content on social media, and creating unique keywords as store search engines. The existence of this activity provides information that the market is very wide and can be reached through digital articles, and all that is needed is knowledge about digital marketing.